Family Ecological Transaction for Disaster Risk Reduction: Case of Anak Dalam Tribe in Bukit Dua Belas National Park, Air Hitam Regency, Jambi, Indonesia - Euis Sunarti; Aliya Faizah Fithriyah; Elwamendri Elwamendri; Suandi Suandi; Fuad Muchlis (International Journal of Disaster Management, 2023)
Anak Dalam Tribe (ADT) is an indigenous community living inside the conservation area, protected as cultural heritage. ADT family is highly dependent on the forest, they used to live and fulfill all their needs from the forest. Now with the modernization and regulatory dynamics taking place, ADT family undergoes changes as a form of adaptation, leading to residing categorization i.e. traditional, transition, and bediom. The changes impact on the ecological transactions thus bring a greater potential risk of forest fires, as has happened in recent years. This study aims to discover ADT family ecological transactions based on their residing type so that potential environmental exposure can be predicted and anticipated for disaster risk reduction. The qualitative research was conducted using a cross-sectional method. Data were collected through in-depth interview, observation, and forum group discussion. Mapping was done to understand the transaction pattern. This study found that the pattern of each kampong was different, showing that development has happened following the socio-ecological changes of each kampong, either by nature or intervention from outside parties. However, the livelihood area is still the biggest and outermost area of all six kampongs despite the residing type, covering the forest area. Moreover, the area of exposure is enlarged. It vindicates the escalating disaster risk. It is suggested to create a holistic livelihood ecosystem for ADT near their residing place to minimize the disaster risk. Political identity of ADT also should be reconsidered, with the inevitable global development, how far the heritage should be kept.